Analysis of the Effect of Average Years of Schooling and Provincial Minimum Wages on the Human Development Index Across 38 Provinces in Indonesia (2024) - Fadhilah, M. Farid; Salsabila, Misfah; Aufa, Faisa Syahda; Yulianti, Oliviani; Sabila, Ratu Salza Alya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The Human Development Index (HDI) is a key indicator for assessing development progress through three dimensions: health, education, and standard of living. This study is motivated by persistent disparities in HDI achievements across Indonesian provinces, where western regions generally show higher development performance compared to eastern regions that continue to face limited access to basic services, inadequate infrastructure, and lower human capital quality. These differences indicate that national improvements in HDI have not yet reflected equitable development.The purpose of this research is to analyze HDI trends across 38 provinces in Indonesia, identify factors contributing to regional gaps, and examine the influence of Average Years of Schooling (AYS) and the Provincial Minimum Wage (PMW) on HDI in 2024. This study uses secondary data from the Central Bureau of Statistics and employs a descriptive approach combined with multiple linear regression using SPSS. The analytical procedures include classical assumption tests, the F-test, t-test, correlation analysis, and the coefficient of determination to assess model feasibility and the significance of each variable.The results show that education and wage policies play an important role in improving HDI, particularly through greater access to education, enhanced public services, and improved living standards. These findings provide policy implications for provincial governments to promote more balanced development, especially by strengthening education, expanding healthcare services, and improving economic welfare in less developed regions.